LATIHAN DRIBBLE TERHADAP KECEPATAN DRIBBLING PADA PEMAIN U14-U15 SSB UNIBRAW 82 KOTA MALANG - Tri Adi Subekti; Supriyadi Supriyadi; Rias Gesang Kinanti (Universitas Negeri Malang, 2017)
Abstract: Dribbling is an effort to kick the ball with a dashed ball position not far from the foot while running to achieve a certain goal in the game of football. To be able to have a good dribbling technique, a soccer player should often practice and pay attention to aspects of supporters in order to perform dribbling well. With the right dribbling and trained then a football player will be able to get past the opponent easily and to look for opportunities to give the ball bait to a friend appropriately. Just like in SSB Unibraw 82 Malang City. This study aims to determine whether there is an effect of dribble training pattern on dribbling speed on U14-U15 SSB Unibraw 82 Malang. The samples used amounted to 20 people. After doing treatment in the form of 10 variations of exercise model then performed the final test (posttest). Based on the results of pretest and posttest data that have been analyzed using Statistical Package for Social Science (SPSS) is known significant value of 0.000 which means that dribble exercise pattern that has been done has a significant influence on dribbling speed on U14-U15 SSB Unibraw 82 Malang.Keywords: Football, exercise, dribble, dribbling, speed.